An interdisciplinary approach for integrating landscape management in the Common Agricultural Policy: Application to the municipality of Mertola, Southern Alentejo, Portugal (ROLE OF BIODIVERSITY CONSERVATION IN THE TRANSITION TO RURAL SUSTAINABILITY, 2004)
This paper seeks to present the methodological approach of a case-study at a local scale, in the south of Portugal, where the European Union Common Agricultural Policy (CAP) has significant impacts in terms of environment, socioeconomic and landscape aspects. The municipality of Mertola is located in the south-eastern part of the Alentejo Region, in a marginal area in relation to socio-economic parameters and agricultural production. As in the region as a whole, the dominant land use system is the Montado in a diversified pattern, which has in the last decades been subject. to successive significant changes, raising questions as to future landscape quality, identity and the required management. As in other European rural areas, the transformations in agriculture and the productive function resulted in changes in the landscape, which have impacts also on other functions such as conservation, environment balance, recreation, life support and preservation of cultural identity. These other functions attract each day more attention as a possible set of alternatives uses in marginal areas of Europe, such as Mertola. This actual context requires thus a landscape management based on integrated policies for the rural world, following the new perspectives of the CAP but also based on a deep knowledge of local landscape dynamics and requirements for preservation of identity. This project intends to evaluate and understand: (a) the changes that have occurred in the municipality in the last decades; and (b) how they have affected landscape pattern and also people's perception and connections to this landscape identity. The intent is to build up proposals for a more integrated and locally adapted formulation of CAP objectives and instruments. This paper will present the changes in landscape pattern and character registered in the study area for the last decades, the interdisciplinary methodology adopted, as well as the results of the first phase of the project.